Educational management strategies: linking infrastructure, student activities, and academic performance - Paul Arjanto; Rivaldo Paul Telussa (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research examines how educational facilities impact school participation, student activities, and educational outcomes in Indonesia, highlighting the urgent need for improved infrastructure. Using 2023 data from the Central Statistics Agency, this study analyzes various indicators such as the number of schools, classroom conditions, sanitation, teacher numbers, and educational outcomes across different regions. Structural Equation Modeling (SEM) is employed to test the relationships among these variables. The findings show that while educational facilities are reliable and valid, enhancing them alone does not guarantee better educational outcomes or increased school enrollment. Other factors like teaching quality and socioeconomic support are crucial. Improved facilities do, however, boost student engagement in extracurricular activities, which is essential for skill development and motivation. The study reveals a positive correlation between school participation and educational outcomes, emphasizing the need for strategies to improve attendance and engagement. It highlights the importance of a holistic educational approach that integrates both academic and extracurricular activities. Policymakers and educators should adopt comprehensive strategies, including improving facilities, teaching quality, and providing socioeconomic support, to maximize educational outcomes and ensure long-term success.